Lack of association of OPRM1 genotype and smoking cessation. - Munafò, MR; Johnstone, E; Aveyard, P; Marteau, T (Oxford University Press, 2013)
INTRODUCTION: Previous studies have reported an association between μ-opioid receptor (OPRM1) genotype and smoking cessation, with some evidence that the strength of this association depends on dose of nicotine replacement therapy (NRT). We examined whether a single-nucleotide polymorphism in the OPRM1 gene is associated with cessation and whether this variant moderates the effects of higher doses of NRT on abstinence. METHODS: Participants were recruited from the practices of primary care physicians in the United Kingdom. Patients smoking an average of at least 10 cigarettes a day, who wanted to quit and were 18 years or older were eligible for inclusion. A total of N = 633 participants were recruited into the original trial, of whom complete data for pharmacogenetic analyses were available on n = 598. Logistic regression was used to test for the effects of OPRM1 genotype and NRT dose, including the genotype × dose interaction term, on smoking status at 4-week, and 26-week follow-up. Analyses were adjusted for potential confounders. RESULTS: There was no evidence of a genotype effect at either follow-up, and no evidence of a genotype × dose interaction effect. CONCLUSIONS: OPRM1 genotype may not affect the likelihood of smoking cessation, and it may not influence response to high- versus low-dose NRT. OPRM1 may have at most only a modest role in explaining cigarette smoking and cessation.